Vehicle-induced dynamic stress analysis of orthotropic steel decks of cable-stayed bridges. Issue 8 (2nd August 2020) - Cui, Chuang; Xu, You-Lin; Zhang, Qing-Hua; Wang, Feng-Yang
Abstract: Orthotropic steel deck (OSD) is widely used in long-span cable-stayed bridges, but vehicle-induced dynamic stresses at its deck-to-rib (DTR) joints often make OSD vulnerable to local failure or fatigue damage. This paper presents a framework for vehicle-induced dynamic stress analysis of DTR joints of OSD in a cable-stayed bridge. The multi-scale finite element model of the bridge is first developed using solid elements to simulate DTR joints of OSD interacted with pavement (local model), shell elements to simulate the most vulnerable girder segment (intermediate model), and beam/truss elements to simulate the rest part of the bridge (global model). Road vehicles are modelled as a combination of several rigid bodies connected by a series of springs, dampers and pivots. The vehicle-induced dynamic stress responses at the DTR joints of a long-span cable-stayed bridge are finally computed to assess the effects of bridge dynamics, vehicle dynamics, asphalt pavement temperature, roughness and vehicle velocity. The results show that the dynamically coupled vehicle-bridge system should be considered and that pavement temperature and roughness are two profound factors affecting the stress responses of DTR joints.